Students’ Experience in Vocabulary Memorizing of Adjective by Using TikTok Duet Video - Ichara Sinta; Zulfitri (Merwin Publisher, 2023)
This research aims to determine the researching some of students’ experience of learning and memorizing vocabulary of adjective in class X-1 IPS SMA swasta Cerdas Murni and the students reflecting the experience were participants of english in part of learning english. This research is qualitative and was conducted in juni 2021 on students of class X-1 IPS SMA Swasta Cerdas Murni. In this study the sample was taken by 3 levels of students in the class, the lowest, the average, and the highest. Each the level taken 2 students. Data were collected through observation and interview. Then the data collected by conducting research. Based on the results of the study, it is known that the students' can be concluded that the TikTok duet video is very helpful for them in memorizing adjective vocabulary. They really enjoy doing it and it's pretty easy because the TikTok app is the one they use most of the time. The TikTok duet video application can also improve their memorizing, especially vocabulary adjectives, which they think that this application is only used for entertainment but in fact can be used as a learning medium.